Urbanization in the west of São Paulo state and the formation of technogenic features - Silva, Érika Cristina Nesta; Dias, Marcel Bordin Galvão [UNESP]; Nunes, João Osvaldo Rodrigues [UNESP]; Oliveira, Antonio Manoel Dos Santos; De Oliveira, Adriana Aparecida (Instituto Geologico, 2019)
The processes of land use and occupation, which develop and transform urban and rural environments and are carried out by societies over time, are also responsible for the formation of technogenic features. During urbanization, societies change the characteristics of the physicalbiotic environment (rock-relief-soil-climate-vegetation-fauna) for the development of several activities. On the other hand, the activities carried out by the societies are influenced by the possibilities arising from the physical-biotic aspects. Regarding the relief, it is important to mention that it is affected in an uneven and differentiated way by society, which is constituted by several social agents and whose actions are part of an extensive process combined and related to the capitalist logic of urban space production. The same happens in rural areas where, especially in the west of São Paulo State (Brazil), changes in vegetation cover and, consequently, in other features of the biotic and physical environment, such as soil and relief, occurred as a result of the expansion of coffee and cotton plantations and livestock farming. This paper answers questions related to the processes of agricultural expansion, urbanization, and their relationship with technogenic formations in the west of São Paulo. In the initial phases of this occupation these formations are related to the erosion intensified by the action of society and to consequent deposition of sediments on valley bottoms. A study was conducted in the east part of the city of Presidente Prudente - SP, showing aspects of urban expansion and describing the formation and evolution of technogenic features. Therefore, for understanding technogenic features, a comprehensive knowledge of the relationship between society and nature is required, based on procedures including field and visualization of aerial photographs from different periods and a retrospective analysis of land use and occupation.
A urbanização do oeste paulista E A formação de feições tecnogênicas
Keywords: Land use and occupation; Presidente Prudente - SP; Technogenic formations; West of São Paulo State (Brazil)